The economic effects of epidemics: from SARS and MERS to COVID-19 - Ceylan, Rahmiye Figen; Ozkan, Burhan (Research Journal in Advanced Humanities, 2020)
Around the end of 2019 through to 2020, the world had to encounter an outbreak of the novel COVID-19, a globally devastating virus, leading to mass losses and socio-economic panic. The impacts of previous SARS-COV and MERS-COV on macro-economic conditions, income level and labour market composition of 26 selected countries were evaluated within this paper in order to make economic inferences for COVID-19. The evaluation signed that the more fatal SARS-COV had depreciating effects on all economies in the sample, while MERS-COV had affected a more limited number of countries. Yet, the past epidemics mostly affected the labour market and services sector, as emphasized by the literature on economics of epidemics. It can be foreseen that, the services sector will be affected negatively with supply and labour demand aspects even after the end of the COVID-19 pandemic. On the other hand, changing consumption attitudes and the rising tendency for online shopping may lead a closer correlation between agriculture and services sectors in terms of delivery services. It might be possible to understand such impacts as more micro-data can be analysed in the future.